Mangrompo Tondok Toraja Traditional Rituals Facing Covid-19 In The Tallu Kalo'na Traditional Region Lembang Gasing Mengkendek District - Sumiaty Sumiaty; Deltiana Saputri Samara (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This study aims to (1) determine the series of ritual processions and (2) find out the symbolic meaning contained in theritual Mangrompo Tondok. Mangrompo Tondok is a ritual of worship or a request for protection to Puang Matua. This research is a descriptive qualitative research. Research informants were determined by non-probability sampling. The primary data is done through observation(observation)and interviews with parties related to the research and secondary data is done through library(libraryresearch)by reviewing some of the literature that is closely related to the issues to be discussed. The data that has been collected is then presented in the form of anarrative realism and analyzed qualitatively. The results showed that (1) the procession of theritual Mangrompo Tondok consisted of the rituals of Ma'kapuran Panggan, Mangkaro Bubun, Ma'bugi, and Mangrompo Tondok (2) the meaning of Mangrompo Tondok for the indigenous peoples of the Tallu Kalo'na Lembang Gasing area is hope for Puang Matua to protect the indigenous people of Tallu Kalo'na Lembang Gasing from the threat of the COVID-19 outbreak.